Humor gráfico: o sorriso pensante e a formação do leitor - Silva, Ivam Cabral da (2008)
This research investigates the graphic humor, in particular the political cartoon and the cartoon, texts characterized by mixing visual-oral language, and its contribution in the formation of the reader. Recovers the main theories about the comicality in general and verifies the presence of these concepts into the texts of graphic humor and how they articulate themselves within the process of seducing the reader. Grounded in the studies of Umberto Eco about the cultural industry products and its relations with the literary theories and the aesthetics reception. After analysing texts of graphic humor, the study concludes that the triad, image-word-humor reveal a sophisticated arrangement which allows the reader to practice effectively the political cartoons and cartoons of production, of sense, cooperating in such a singular manner to the formation of a reflexive reader